THE EFFECT OF BRAND ELEMENT CRITERIA AND BRAND IMAGE OF PRIVATE LABEL PRODUCTS ON STORE IMAGE AND ITS IMPLICATIONS ON CUSTOMER LOYALTY - Annas, Mohammad; Pramudito, Eko Sigit (IMAGE : Jurnal Riset Manajemen, 2021)
This study aims to analyze the effects and aspects of store images and customers loyalty. Independent variable in this research is criteria of brand element and brand image, and dependent variables are store image and customer loyalty. This research were using questionnaires collected from 302 respondents who buy products with private label brand on their shopping baskets during Pandemic Covid-19 period. The result showed that brand element criteria had significant effect on store image and the same as brand image gave significant effect on store image, and store image significantly affect the customer loyalty. The conclusion derived from this study was to keep the private brand element criteria on the sight of customer side, maintain its good image because the brand effecting also the store image where the private label brand sold. Reinforcing store image periodically to maintain its customer loyalty should be done periodically and frequently.Â Keywords: Private label;Private Brand;Brand Element;Brand Image;Store Image